When does the communication of group-based anger increase outgroup empathy in intergroup conflict? The role of perceived procedural unfairness and outgroup consensus. (June 2018) - de Vos, Bart; van Zomeren, Martijn; Gordijn, Ernestine H.; Postmes, Tom
Increasing outgroup empathy is an important first step toward reducing intergroup conflict. The communication of group-based anger has been found to increase outgroup empathy due to its presumed relational function (as it signals to the outgroup that they unfairly treat the ingroup, but also that the ingroup wants to maintain a positive intergroup relationship). Yet, little is known about when communicating group-based anger increases outgroup empathy. We therefore examine two antecedent conditions, namely perceived procedural unfairness (which makes the communication of anger more appropriate) and outgroup consensus (which makes the communication of anger more group-based). Three experiments suggest that the communication of group-based anger increases outgroup empathy only when the outgroup was treated unfairly (Experiment 1) and when there was high outgroup consensus (Experiment 2). Results from Experiment 3 revealed that either antecedent seems sufficient to facilitate the positive, empathy-inducing effects of the communication of group-based anger. We discuss the implications of these findings for the theory and practice of communicating anger in intergroup conflicts to increase outgroup empathy.